Biodistribution and Radiation Dosimetry of the Integrin Marker 64Cu-BaBaSar-RGD2 Determined from Whole-Body PET/CT in a Non-human Primate - Liu, Shuanglong; Vorobyova, Ivetta; Park, Ryan; Conti, Peter S. (Frontiers in Physics, 2017)
Introduction:64Cu-BaBaSar-RGD2 is a positron emission radiotracer taken up by integrin αvβ3, which is overexpressed in many malignancies. The aim of this study was to evaluate the biodistribution of 64Cu-BaBaSar-RGD2 in a non-human primate with positron emission tomography (PET) and to estimate the absorbed doses in major organs for human. Materials and Methods: Whole-body PET imaging was done on a Siemens Biograph scanner with a male macaque monkey. After an i.v. injection of 13.1–19.7 MBq/kg of 64Cu-BaBaSar-RGD2, whole body scan was collected for a total duration of 180 min. Attenuation and scatter corrections were applied to reconstructions of the whole-body emission scan. After image reconstruction, three-dimensional volumes of interest (VOI) were hand-drawn on the PET transaxial or coronal slices of the frame where the organ was most conspicuous. Time-activity curves (TACs) for each VOI were obtained, and residence times of each organ were calculated by integration of the time-activity curves. Human absorbed doses were estimated using the standard human model in OLINDA/EXM software. Results: Injection of 64Cu-BaBaSar-RGD2 was well-tolerated in the macaque monkey, with no serious tracer-related adverse events observed. 64Cu-BaBaSar-RGD2 was cleared rapidly from the blood pool, with a 12.1-min biological half-life. Increased 64Cu-BaBaSar-RGD2 uptake was observed in the kidneys, and bladder, with mean percentage injected dose (ID%) values at 1 h after injection ~35.50 ± 6.47 and 36.89 ± 5.48, respectively. The calculated effective dose was 15.30 ± 2.21 μSv/MBq, and the kidneys had the highest absorbed dose at 108.43 ± 16.41 μGy/MBq using the non-voiding model. For an injected activity of 925 MBq 64Cu for human, the effective dose would be 14.2 ± 2.1 mSv. Discussion: Due to the limited availability of the primates, we evaluated 64Cu-BaBaSar-RGD2 in the same monkey using three imaging sessions. Measured absorbed doses and effective doses of 64Cu-BaBaSar-RGD2 are comparable to other reported RGD-derived radiopharmaceuticals labeled with 64Cu and 18F. Therefore, 64Cu-BaBaSar-RGD2 can be safely injected into humans for studying integrin αvβ3 expression non-invasively.